The Influence of PNM Mekar Syariah Microfinance on the Welfare of MSMEs in Parungpanjang, Bogor Regency - Amin, Muhamad; Bahri, Syaeful; Mabruroh, Ahda Inayati; Mahmud Syukri (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2024)
PNM Mekar Syariah Financing is a business capital loan service that implements a joint liability system and is carried out in groups. This study examines the Effect of PNM Mekar Syariah Micro Financing on Improving the Welfare of MSMEs in Bogor Regency. The study uses a quantitative approach with a questionnaire method as a data source, through five stages of testing: Validity Test, Reliability Test, Classical Assumption Test, with the help of SPSS Version 2023 software and Microsoft Excel 2013. The results of the study can be concluded that there is a positive and significant effect of PNM Mekar Syariah financing on improving the welfare of MSMEs in Bogor Regency. Simple Linear Regression Equation: The resulting equation is Y = 27.416 + 0.323X + εY = 27.416 + 0.323X + = 27.416 + 0.323X + ε, with a regression coefficient of the financing variable (X) of 0.323. This shows that every one unit increase in financing has the potential to increase the welfare of MSMEs by 0.323 units. T-test: The results of the hypothesis test show that t count = 3.851t count = 3.851t count = 3.851 with a significance value of <0.001, smaller than the significance limit of 0.05. With t count> t table (3.851> 1.66412)t count > t table (3.851 > 1.66412)t count> t table (3.851> 1.66412), H0 is rejected, and H1 is accepted. This means that the financing variable (X) has a significant effect on increasing MSMEs (Y). Determination Coefficient (R Square): The R Square value of 0.372 indicates that PNM Mekar Syariah financing affects the Increase in MSME Welfare by 13.8%. This means that 86.2% of the variation in MSME performance is influenced by other factors not included in this study.